Efficacy and safety of ivacaftor in patients with cystic fibrosis who have an Arg117His-CFTR mutation: a double-blind, randomised controlled trial. Issue 7 (July 2015) - Moss, Richard B; Flume, Patrick A; Elborn, J Stuart; Cooke, Jon; Rowe, Steven M; McColley, Susanna A; Rubenstein, Ronald C; Higgins, Mark; VX11-770-110 (KONDUCT) Study Group
Summary Background Ivacaftor has been previously assessed in patients with cystic fibrosis with Gly551Asp-CFTR or other gating mutations. We assessed ivacaftor in patients with Arg117His-CFTR, a residual function mutation. Methods We did a 24-week, placebo-controlled, double-blind, randomised clinical trial, which enrolled 69 patients with cystic fibrosis aged 6 years and older with Arg117His-CFTR and percentage of predicted forced expiratory volume in 1 s (% predicted FEV1) of at least 40. We randomly assigned eligible patients (1:1) to receive placebo or ivacaftor 150 mg every 12 h for 24 weeks. Randomisation was stratified by age (6–11, 12–17, and ≥18 years) and % predicted FEV1 (<70, ≥70 to ≤90, and >90). The primary outcome was the absolute change from baseline in % predicted FEV1 through week 24. Secondary outcomes included safety and changes in sweat chloride concentrations and Cystic Fibrosis Questionnaire-Revised (CFQ-R) respiratory domain scores. An open-label extension enrolled 65 of the patients after washout; after 12 weeks, we did an interim analysis. Findings After 24 weeks, the treatment difference in mean absolute change in % predicted FEV1 between ivacaftor (n=34) and placebo (n=35) was 2·1 percentage points (95% CI −1·13 to 5·35; p=0·20). Ivacaftor treatment resulted in significant treatment differences in sweat chloride (−24·0 mmol/L, 95% CI −28·01 to −19·93; p<0·0001) and CFQ-R respiratory domain (8·4, 2·17 to 14·61; p=0·009). In prespecified subgroup analyses, % predicted FEV1 significantly improved with ivacaftor in patients aged 18 years or older (treatment difference vs placebo: 5·0 percentage points, 95% CI 1·15 to 8·78; p=0·01), but not in patients aged 6–11 years (−6·3 percentage points, −11·96 to −0·71; p=0·03). In the extension study, both placebo-to-ivacaftor and ivacaftor-to-ivacaftor groups showed % predicted FEV1 improvement (absolute change from post-washout baseline at week 12: placebo-to-ivacaftor, 5·0 percentage points [p=0·0005]; ivacaftor-to-ivacaftor, 6·0 percentage points [p=0·006]). We did not identify any new safety concerns. The studies are registered with ClinicalTrials.gov (the randomised, placebo-controlled study, number NCT01614457; the open-label extension study, number NCT01707290). Interpretation Although this study did not show a significant improvement in % predicted FEV1, ivacaftor did significantly improve sweat chloride and CFQ-R respiratory domain scores and lung function in adult patients with Arg117His-CFTR, indicating that ivacaftor might benefit patients with Arg117His-CFTR who have established disease. Funding Vertex Pharmaceuticals Incorporated.